Qatar's challenge to Saudi Arabia : an alternative view of Wahhabism - Dorsey, James M. (2013)
Qatar, whose native population adheres to the Wahhabi creed, poses a major challenge to the puritanical interpretation of Islam of Saudi Arabia, which seeks to make itself impervious to the push for greater freedom, transparency and accountability sweeping the Middle East and North Africa.